Evaluation the performance of co-encapsulated beads formed with a probiotic culture and L-ascorbic acid against pathogens and simulated gastric conditions - and Subrota Hati, Koushik Das, Kunal M Gawai, Mitesh Hingu, Ashish Shendurse (Indian Journal of Dairy Science, 2025)
The present investigation was conducted on beads formed from extrusion and emulsion methods having a co-encapsulated probiotic culture and L-ascorbic. These were tested against pathogens and simulated gastric conditions. gastric juice tolerance of encapsulated probiotic culture has been shown. Comparing treatment means, there was a significant difference (p<0.05) and mean cell viability was significantly higher for emulsion method compared to extrusion method. The results of study for survival of probiotic viability in simulated gastro-intestinal conditions showed that treatment wise there was a significant difference (p<0.05) and mean cell viability was significantly higher for emulsion method compared to extrusion method. Similarly, the results of study for changes in ascorbic acid concentration in simulated gastro-intestinal conditions showed that treatment wise there was a significant difference (p<0.05) and mean concentration was significantly higher for emulsion method compared to extrusion method. For antimicrobial activity, four samples were prepared - control sample (C), encapsulated culture by emulsion method (Em), extrusion method (Ex), heat treated free cells (H). Em sample showed highest inhibition zone (16.33±2.08 mm) against Enterococcus faecalis ATCC 29212 and lowest inhibition zone (12.7± 0.58 mm) was observed against E. coli MTCC 1687 and Staphylococcus aureus MTCC 7373. For Ex sample, highest inhibition zone (14.00±1.0 mm) was seen against Enterococcus faecalis ATCC 29212 and lowest inhibition zone (9.07± 1.15 mm) was observed against Staphylococcus aureus MTCC 7373. The beads from emulsion method survived better (p<0.05) in simulated gastro intestinal conditions than beads from extrusion method in terms of cell viability and AA concentration. Additionally, the beads from emulsion method survived better (p<0.05) in acidic solution than beads from extrusion method in terms of cell viability and AA concentration. Hence, emulsion method could be the better methods for protecting sensitive ingredients and such prepared co-encapsulated beads offers better option in delivering functional items to individuals via foods.